Multiplication E-Module Media to Improve Cognitive Ability of First Grade Elementary School Students - Amanda, Niken; Kanzunnudin, Mohammad; Fathurohman, Irfai (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
In this digital era there are still many schools that have not used IT-based learning media, especially in the content of mathematics lessons on multiplication material. Even though mathematics is one of the subjects that must be achieved in elementary school education. Many students think mathematics is very difficult and complicated. This is because there are many ways to solve problems in everyday life that use calculations. This study aims to analyze the need for valid and practical media development and to analyze the effectiveness of media results for improving students' cognitive abilities. The type of research used in this research is Research and Development. The development of the multiplication e-module uses the Borg and Gall development model design. The data obtained from the media development needs questionnaire. Data analysis uses the Guttman scale. The results of the study showed that the multiplication e-module media is needed to improve the cognitive abilities of second grade elementary school students. The results of the media validity test obtained results that were very feasible to use. While the results of the practicality test of teachers and students obtained very practical results. While the results of the effectiveness test showed that the increase in cognitive abilities in the experimental class was higher than the control class.